2020
DOI: 10.1186/s43019-020-00040-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypoalbuminemia and obesity class II are reliable predictors of peri-prosthetic joint infection in patient undergoing elective total knee arthroplasty

Abstract: Background: Malnutrition is a common and modifiable risk factor for postoperative complications and adverse outcomes in orthopedics. The purpose of this study was to identify biomarkers of malnutrition in patients undergoing elective total knee arthroplasty (TKA) that are predictive of adverse in-hospital postoperative complications, to facilitate the identification of at-risk patients for nutritional optimization before surgery. Methods: A total of 624 patients who underwent elective TKA between 2013 and 2017… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 38 publications
0
19
0
Order By: Relevance
“…A recent report projected the obesity trend in 2030 that the number of people who are overweigh might reach a total of 2.16 billion and another 1.12 billion obese population, or 38% and 20% of the world's adult population respectively [ 47 ]. Mean BMI of patients in our previous studies always fell within “overweight” or “obese” categories [ 48 50 ]. Consequently, a PRO questionnaire for patients underwent TKA is important to provide accurate and high responsiveness to the respondents (patients) who are “overweight” or “obese”.…”
Section: Discussionmentioning
confidence: 98%
“…A recent report projected the obesity trend in 2030 that the number of people who are overweigh might reach a total of 2.16 billion and another 1.12 billion obese population, or 38% and 20% of the world's adult population respectively [ 47 ]. Mean BMI of patients in our previous studies always fell within “overweight” or “obese” categories [ 48 50 ]. Consequently, a PRO questionnaire for patients underwent TKA is important to provide accurate and high responsiveness to the respondents (patients) who are “overweight” or “obese”.…”
Section: Discussionmentioning
confidence: 98%
“…Albumin is well known among clinicians for its reliability and sensitivity for assessing nutritional status [16]. Hypoproteinemia can lead to a signi cantly higher incidence of postoperative complications including delayed wound healing due to reduced collagen synthesis and protein matrix deposition [17,18] and super cial or deep infection caused by diminished immune response [19], and adverse events such as myocardial infarction, cardiac arrest, stroke and even mortality in TJA [10,18].…”
Section: Discussionmentioning
confidence: 99%
“…This population accounts for the majority of patients undergoing TKA. Fortunately, compared with emergency operation, the elective nature of TJA allows these patients to have an adequate preoperative nutritional storage for reducing the risk of postoperative HAS use [16,25]. One study [26] reported that a high-protein diet could improve the overall survival for older adults diagnosed with advanced gastrointestinal cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, undernourished patients with low body mass index are also at an increased risk of PJI [ 30 ]. The unifying link between underweight patients, overweight patients, and those who underwent weight reduction surgery that results in increased PJI risk may be nutritional deficits [ 31 ]. Malnutrition and obesity are both conditions that are linked to dysfunction of the microbiome, as obese and undernourished patients both have reduced diversity of the gut microbiota [ 32 ].…”
Section: Proposed Solutionmentioning
confidence: 99%